Profit Shifting and FDI Restrictions - Mathilde Lebrand (Center for Economic Studies and ifo Institute (CESifo), 2016)
Tariffs have almost completely disappeared but various restrictions on foreign entry remain for multinationals. Many trade agreements and Bilateral Investment Treaties (BITs) have been signed to lower tariffs and reduce the risks of expropriation. Why do we see so few agreements removing FDI entry barriers? Could the contemporary rise of tax havens where multinationals can shift their profits explain the absence of FDI agreements? In this paper I develop a model in which governments can restrict the entry of foreign affiliates and multinationals can shift their profits across countries. I first demonstrate that the possibility for multinationals to repatriate their profits is a determinant of FDI restrictions. An agreement can solve for the resulting inefficiency. However, I show that an agreement is made unnecessary when (i) there is foreign lobbying that pushes for more entry, or when (ii) firms can shift profits to tax havens. Tax treaties that reduce profit shifting would be a first step towards more agreements that reduce FDI restrictions. I conclude by providing empirical evidence that profit shifting affects the choice of FDI restrictions.
Keywords: F23; D43; D72; F13; 330; FDI; multinationals; investment agreements; lobby; profit shifting